2022
DOI: 10.1055/a-1835-1877
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Brain Alterations in Type 1 Diabetes – Findings Based on Detailed Phenotyping of Neuropathy Status

Abstract: Aims This study investigated brain structure in patients of type 1 diabetes with diabetic peripheral neuropathy (DPN) and type 1 diabetes with neuropathic pain and the associations to clinical, peripheral, and cognitive measurements. Methods Sixty individuals with type 1 diabetes and 20 healthy controls were included in the study. Nineteen individuals with type 1 diabetes and neuropathic pain, 19 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“…The study was conducted between August 2019 and February 2022 in participants from the "MEDON" (Methods for Early Detection Of diabetic peripheral Neuropathy)-cohort (clinicaltrials.gov: NCT04078516) [12][13][14]. This population is described in details elsewhere, but in short, the original cohort consisted of 80 participants equally divided into four groups: participants with T1DM and painful diabetic peripheral neuropathy (PDPN), participants with T1DM and DPN, participants with T1DM and no DPN, and healthy controls (HC) without diabetes or pain [12][13][14]. The four groups were matched 1:1:1:1 on age (+/-2 years) and sex.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted between August 2019 and February 2022 in participants from the "MEDON" (Methods for Early Detection Of diabetic peripheral Neuropathy)-cohort (clinicaltrials.gov: NCT04078516) [12][13][14]. This population is described in details elsewhere, but in short, the original cohort consisted of 80 participants equally divided into four groups: participants with T1DM and painful diabetic peripheral neuropathy (PDPN), participants with T1DM and DPN, participants with T1DM and no DPN, and healthy controls (HC) without diabetes or pain [12][13][14]. The four groups were matched 1:1:1:1 on age (+/-2 years) and sex.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Neuropathic pain severity (over the last 4 weeks) was derived from the PainDETECT questionnaire as average and peak pain intensity rated on a visual analog scale (VAS) ranging from 0-10, where 0 is no pain and 10 is the most intense pain imaginable [18]. Quantitative sensory testing and conventional nerve conduction studies were performed as previously described and reported [12][13][14].…”
Section: Assessment Of Peripheral Nervesmentioning
confidence: 99%
“…No significant differences in total GMV were observed between the three diabetes groups. (82) Overall, these data provide the knowledge that GMV is altered in T1DM regardless of the presence of DPN or neuropathic pain. This was further supported by the lack of association between total GMV and peripheral nerve function.…”
Section: Structural Brain Alterationsmentioning
confidence: 52%
“…(94) In Paper II lower volume of thalamus was observed in the diabetes individuals experiencing neuropathic pain. (82) The structural changes may contribute to the development of neuropathic pain but also to the functional thalamic connectivity alterations observed in the same group in Paper III. This will be discussed later in section 6.3.…”
Section: Structural Brain Alterationsmentioning
confidence: 92%
See 1 more Smart Citation